Salón de Clase Intermediate Spanish for Education Professionals - Castro Ortiz, Fernando; Zimotti, Giovanni (Open textbook library., 2021)
Salón de clase, Intermediate Spanish for Education Professionals is a comprehensive intermediate Spanish open access textbook with reading, listening, speaking, and writing practice for students who have an interest and/or intend to pursue a career in the field of Education (teachers, administrators, counselors, psychologists, social workers, support staff members, paraprofessionals, among others). This Open Education Resource (OER) aims to explore the role of Spanish language and Spanish speakers in the American education system, as well as to improve student communicative abilities in Spanish. Salón de clase integrates interactive activities (h5p), video interviews with Spanish speakers to present authentic materials, and topics related to education. Grammar is not presented as a standalone topic, but it is seemly integrated into all parts of this book.